BEYOND RENAL FUNCTION: SYSTEMIC AND FUNCTIONAL ASPECTS OF CKD IN THE ELDERLY - Marcin Lampart; Hanna Skarakhodava; Agnieszka Floriańczyk; Ewa Romanowicz; Aleksandra Kołdyj; Agnieszka Ozdarska; Adrian Krzysztof Biernat; Anna Rupińska; Katarzyna Kozon; Kamila Krzewska (International Journal of Innovative Technologies in Social Science, 2025)
Chronic kidney disease is a significant contributor to increased morbidity, mortality and reduced quality of life, particularly in elderly individuals. As the greatest prevalence of CKD occurs in the oldest age group, the growing life expectancy and aging population suggest a continued rise in CKD incidence. The disease frequently coexists with other common conditions, such as hypertension, diabetes, heart failure complicating both diagnosis and treatment. Moreover, the cost of managing a dialysis-dependent population is substantial and is expected to rise. The article aims to highlight the systemic nature of CKD, in which the progressive impairment of homeostatic function triggers a chronic inflammatory process. This leads to accelerated cellular aging, predominantly affecting blood vessels, heart, brain tissue, muscles and diminishing the remaining renal function. The accumulation of uremic toxins, electrolyte imbalances and fluid overload impairs cognitive performance, reducing both functional capacity and adherence to medical treatment. Disruptions in phosphates-calcium metabolism contribute to mineral-bone disease. The loss of muscle and bone mass leads to reduced mobility and physical endurance, thereby increasing the risk of falls, injury, disability and death. These factors are the main components of the Frailty Syndrome, for which CKD is a major underlying cause, a condition characterized by increased vulnerability to minor stressors and reduced ability to recovery and serious worsening of general health condition. This review provides a comprehensive overview, pathophysiological mechanism, clinical manifestations, functional consequences and management strategies in elderly patients with CKD.